UJI KUALITATIF ANALISIS KANDUNGAN METAMFETAMIN DARI RAMBUT PENGGUNA SABU-SABU MENGGUNAKAN METODE KOLOM EKSTRAKSI - Nur Asyiah Dalimunthe (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2021)
Methamphetamine is a stimulant, with a stronger stimulant effect than cocaine or other natural stimulants. Use in large quantities can cause